Analisis Pemanfaatan Limbah Tandan Kosong Kelapa Sawit Dalam Produktivitas Kerja Karyawan PT Cipta Usaha Sejati - Tussa Balsia, Monik Nomi; Purwaningsih, Endang; Kuswanti, Heni (Universitas Tanjungpura, 2024)
The target of this research is to find information on the process of processing empty oil palm bunch waste, the impact of processing empty palm fruit bunch waste which creates a comfortable working environment, the impact of a comfortable working environment on work productivity. This research uses a qualitative approach with a case study method, involving 5 employees of PT Cipta Usaha Sejati. Data was collected through interviews, observation, documentation, and analyzed using the Miles and Huberman model, and the validity of the data was checked using triangulation techniques and using reference materials. The research results show that there is the availability of empty palm oil bunch waste and the processing of empty palm oil bunch waste carried out by PT Cipta Usaha Sejati produces products in the form of chopped tangkos and ash which is used as compost fertilizer. The waste processing carried out can affect the employee's work environment in 3 aspects, namely: (1) Layout of empty oil palm fruit bunch waste (2) Cleanliness of the work environment (3) Air circulation, which means that with this waste processing, the work environment around the waste disposal site be neat and orderly. Because a work environment that is neat and organized also has a positive impact on employee work productivity with 4 aspects: (1) Ability to motivate oneself (2) Build self-confidence (3) be responsible at work (4) make a positive contribution.